PENGARUH BERAT BADAN TIDAK NAIK TERHADAP PERTUMBUHAN PADA BAYI 6-12 BULAN DI KABUPATEN BOGOR - Minarto . (GIZI INDONESIA, 2006)
The objective of the study is to examine the effect of not gaining weight on growth achievement and to identify its risk factors. The design of the study is a prospective cohort. Some 219 6-month old infants met sample inclusion criteria at enrollment (did not suffer from chronic diseases, had normal nutritional status, and the parents willing to involve in the study). The data collected include weight and length, morbidity, food consumption and child care practices, and socio-economic status of the family. The weight of infant was measured using SECA digital scale, and length was measured using standardized length board. Precision and accuracy test was carried out based on WHO procedure. The study found that the frequency and consecutive events of not gaining weight have a significant effect on weight achievement at 12 months of age. The differences of weight increment from 6 to 12 months between infants who did not experience growth failure and those who did not gain weight 1 time, 2 times, and 3 times were 200 grams, 450 grams and 1150 grams respectively. The frequency and consecutiveness of not gaining weight was associated with food consumption patterns and morbidity status of infants. Further analysis showed that infants suffered from coughing 14 days had risk ratio of 2.2 times (95% CI 1.197-3.930) higher having 2 times not gaining weight than those who suffered 14 days. While, infants suffered from coughing 28 days had a risk ratio of 5 times (95% CI 1.472-15.678) higher having 3 times not gaining weight than those who suffered =28 days. There is no association between the age of not gaining weight with weight achievements at 6 and 12 months. The frequency and subsequent events of not gaining weight of were consistently determining the growth of infant at 12 months of age. Child’s morbidity was significantly associated with the event of 2 times and 3 times not gaining weight. It is recommended that infants who do not gain weight 2 times should have health examination for prompt treatment.